Morphological study and corrosion penetration rate of SAE 5160 steel in saline medium (NaCl): a study by immersion test (Research, Society and Development, 2022)
The metal has numerous applications and characteristics that allow its application in different environmental conditions. However, it is necessary that the steel be produced for a certain condition, as the chemical and physical characteristics of the steel can be affected in case of incompatibility with the environment. Due to the effects that corrosion can have in cases of critical process failure, high costs are involved in maintenance and replacement of parts and equipment. Corrosion studies have grown with the aim of eliminating corrosive effects, based on the prevention and development of steels with greater resistance to the phenomenon. SAE 5160 steel is susceptible to corrosion when under conditions where cathodic reactions can occur, with the presence of oxygen, water and dissolved salts. The objective of this work was to evaluate the behavior of SAE 5160 steel in different concentrations of NaCl in solution, as a way of verifying the effect of the medium on the corrosion of steel using an immersion test for 10 weeks. An applied methodology was applied and, regarding the objectives, an explanatory research. The focus was a qualitative and quantitative research. The effect was checked from the corrosion penetration rate (CPR) to determine the corrosivity of the media. At the end, a metallographic microscope was used to characterize the morphology of corrosion in the specimens (CP's). It is concluded that the SAE 5160 steel showed moderate CPR in the media and the increase in the NaCl content increases the corrosion rate. Alveolar and pitting corrosion formation is observed on the surface of the CP's.